Dynamics and role of the Durban cyclonic eddy in the KwaZulu-Natal Bight ecosystem. (1st June 2016) - Guastella, LA; Roberts, MJ
Abstract : The semi-permanent Durban Eddy is a mesoscale, lee-trapped, cold-core cyclonic circulation that occurs off the east coast of South Africa between Durban in the north and Sezela, some 70 km to the south. When present, strong north-eastward countercurrents reaching 100 cm s –1 are found inshore. It is hypothesised that the cyclone is driven by the strong south-westward flowing Agulhas Current offshore of the regressing shelf edge near Durban. Analysis of ADCP data and satellite imagery shows the eddy to be present off Durban approximately 55% of the time, with an average lifespan of 8.6 days, and inter-eddy periods of 4 to 8 days. After spin-up the eddy breaks loose from its lee position and propagates downstream on the inshore boundary of the Agulhas Current. The eddy is highly variable in occurrence, strength and downstream propagation speeds. There is no detectable seasonal cycle in eddy occurrence, with the Natal Pulse causing more variability than any seasonal signal. A thermistor array deployed in the eddy centre, together with ship CTD data, indicates upward doming of the thermal structure in the eddy core associated with cooler water and nutrients being moved higher in the water column, stimulating primary production. Together with the use of satellite imagery, our findings indicate a second mechanism of upwelling, viz. divergent upwelling in the northern limb of the eddy. Satellite-tracked surface drifters released in the eddy demonstrated the potential for nutrient-rich eddy water to be transported northwards along the inshore regions of the KwaZulu-Natal (KZN) Bight, thus contributing to the functioning of the bight ecosystem, as well as southwards along the KZN and Transkei coasts – both by the eddy migrating downstream and by eddy water being recirculated into the inshore boundary of the Agulhas Current itself.